Manajemen Strategi Inovasi Produk dalam Mendukung Pertumbuhan UMKM: Observasi pada Usaha “3S Teh Cem” - Theysa Sahlani Pratiwi; Siti Rugayah; Mutiara Praptasari (Tamilis Synex: Multidimensional Collaboration, 2024)
An MSME that is developing will always experience challenges that are not small and not easy; with the increasing number of people who want to open a business, the competition against other business actors will become tighter, and every MSME business actor will increasingly be faced with various challenges such as limited labor resources. And will continue to compete with larger businesses. Micro, small, and medium enterprises (MSMEs) such as "3S TEH CEM" are faced with the challenge of continuing to innovate to expand market share and increase revenue. This study uses a qualitative approach to understand the perspectives and experiences of business owners and gain in-depth insight into the innovation strategies implemented in developing products and strengthening branding. The research results show that innovation can be implemented through various strategies, such as providing member cards to increase customer loyalty, creating new menus with various choices, setting up shops with interesting concepts, adding ice cubes, and adding syrup with various fruit flavors by selling iced tea. This syrup, 3S Teh Cem, also has a unique recipe to provide various drink choices to consumers; 3S Teh Cem MSMEs have information on the elements of management aspects in the implementation procedures of 3S Teh Cem, which will greatly influence how they will continue to develop innovation. To make this business a bigger business, it must collaborate with other producers and utilize the services of content creators/influencers to expand marketing reach via social media. This study concludes that innovation is a strategy that cannot be ignored when facing business competition. By implementing the right innovations, "3S Teh Cem" can increase its competitiveness and attract consumer interest with unique and quality products. The suggestions include involving customers through member cards, developing menus and strengthening branding, providing product innovations for health, establishing strategic collaborations with other parties, utilizing social media, and strengthening internal systems to support continuous innovation and skills training for employees. In this way, "3S Teh Cem" can continue to develop and become a major player in the contemporary beverage industry in Indonesia.